1984
DOI: 10.3758/bf03197677
|View full text |Cite
|
Sign up to set email alerts
|

Redefining the regularity effect

Abstract: This study reports two experiments that further explore the regularity effect in single-word pronunciation. Experiment 1 shows that regularity effects are found only with ;rregular words that are "true" exceptions (e.g., PINT, MONK, BROAD). Words that are irregular in terms of grapheme-to-phoneme correspondence rules, but either are regular in terms of a higher order correspondence rule [e.g., PALM, HEALTH) or possess a divergent, although reasonably common, correspondence (e.g., GLOVE, HEAD), produce response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Second, because spelling-to-sound regularity has been demonstrated to interact with word frequency in naming (Seidenberg, Waters, Barnes, & Tanenhaus, 1984), it might be argued that the presence of even one or two irregular words in a lowfrequency condition might slow down the mean decision latency for that condition. However, this is unlikely to be the case, because the advantage for regularly spelled words seen in naming tasks does not always extend to the LDT (see, e.g., Andrews, 1982;Coltheart, Besner, Jonasson, & Davelaar, 1979;Coltheart et al, 1977;Mason, 1978;Parkin, 1982Parkin, , 1984Seidenberg et al, 1984). The question that must now be addressed is how the observed interaction between AoA and frequency arose.…”
Section: Resultsmentioning
confidence: 99%
“…Second, because spelling-to-sound regularity has been demonstrated to interact with word frequency in naming (Seidenberg, Waters, Barnes, & Tanenhaus, 1984), it might be argued that the presence of even one or two irregular words in a lowfrequency condition might slow down the mean decision latency for that condition. However, this is unlikely to be the case, because the advantage for regularly spelled words seen in naming tasks does not always extend to the LDT (see, e.g., Andrews, 1982;Coltheart, Besner, Jonasson, & Davelaar, 1979;Coltheart et al, 1977;Mason, 1978;Parkin, 1982Parkin, , 1984Seidenberg et al, 1984). The question that must now be addressed is how the observed interaction between AoA and frequency arose.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of regularity were tested using three word lists (Coltheart, Besner, Jonasson, & Davelaar, 1979;Glushko, 1979;Parkin, 1984). All three lists consisted of short (one or two syllable long) morphologically simple content words (there were only two morphologically complex words in Parkin's list, and one function word in Glushko's list).…”
Section: Regularitymentioning
confidence: 99%
“…The former, as originally proposed by Coltheart (1978) and subsequently developed by Morton and Patterson (1980) and Parkin (1984), postulates two functionally independent methods of word processing. One of these is a lexical processing route that operates by the direct mapping of the visual characteristics of a letter string onto its stored lexical representation in the mental lexicon.…”
mentioning
confidence: 99%
“…' Recent modifications to dual-route theory have amended Coltheart's (1978) assertion that the nonlexical route operates solely by the application of GPCs. Shallice, Warrington, and McCarthy (1983) and Parkin (1984) suggested that nonlexical assembly of phonology may also use larger patterns of letters operating beyond the GPC level. If this is the case, some words exhibiting a minor correspondence in terms of Venezky's (1970) rules have a major correWe are grateful to the editor and to two anonymous reviewers for their many helpful comments on earlier versions of this manuscript.…”
mentioning
confidence: 99%